2021
DOI: 10.1007/s11676-021-01375-z
|View full text |Cite
|
Sign up to set email alerts
|

Land cover classification in a mixed forest-grassland ecosystem using LResU-net and UAV imagery

Abstract: Using an unmanned aerial vehicle (UAV) paired with image semantic segmentation to classify land cover within natural vegetation can promote the development of forest and grassland field. Semantic segmentation normally excels in medical and building classification, but its usefulness in mixed forest-grassland ecosystems in semi-arid to semi-humid climates is unknown. This study proposes a new semantic segmentation network of LResU-net in which residual convolution unit (RCU) and loop convolution unit (LCU) are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This holds particularly true in scenarios like the segmentation and classification of vegetation land covers [55]. An illustrative example of this complexity is encountered when attempting to segment the boundaries among ecosystems characterized by a combination of both forest and grassland in regions with semi-arid to semi-humid climates [142].…”
Section: Extracting Boundary Informationmentioning
confidence: 99%
“…This holds particularly true in scenarios like the segmentation and classification of vegetation land covers [55]. An illustrative example of this complexity is encountered when attempting to segment the boundaries among ecosystems characterized by a combination of both forest and grassland in regions with semi-arid to semi-humid climates [142].…”
Section: Extracting Boundary Informationmentioning
confidence: 99%
“…Deep learning methods have the advantages of strong generalization ability, good robustness and higher representation ability in target recognition. Previous studies have shown [2,3] that the use of deep learning methods combined with UAV technology can effectively identify ground objects, especially the UAV image segmentation tasks are extremely widely used. Semantic segmentation can classify images pixel by pixel, which has certain advantages in weed recognition [4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…One of the applications of Remote Sensing is the use of imagery to classify and delineate different objects and land cover types on the Earth's surface, a process that involves collecting field data from a series of samples as an input for training a classification model (Zou and Greenberg, 2019;Prentice et al, 2021). Classification in Remote Sensing involves the categorization of response functions recorded in imagery as representations of real-world objects, according to their spectral similarity to the initial values overlapping the samples, which can provide detailed information about land-cover, specifically in a mixed forest-grassland (Corbane et al, 2015;Cullum et al, 2016;Hamylton et al, 2020;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…According to a study performed by Christian and Christiane (2014), data collected from UAS can capture more information about environment composition and structure. Thus, using UAS high-resolution cameras is one of the most preferred methods to classify land cover in a mixed savannasgrassland ecosystem (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%